2013
DOI: 10.2174/1874325001307010619
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Patients with Knee Osteoarthritis: A Commentary on Nonsurgical and Surgical Treatments

Abstract: Knee osteoarthritis (OA) has a significant negative impact on health-related quality of life (HRQoL). Identification of therapies that improve HRQoL in patients with knee OA may mitigate the clinical, economic, and social burden of this disease. The purpose of this commentary is to report the impact of knee OA on HRQoL, describe the change in HRQoL attributable to common knee OA interventions, and summarize findings from clinical trials of a promising therapy. Nonsurgical therapies do not reliably modify HRQoL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
99
1
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(108 citation statements)
references
References 57 publications
2
99
1
6
Order By: Relevance
“…The physical and psychosocial impairments in individuals with knee OA have an impact on QoL due to their influence on social interactions, mental functioning and sleep quality 7. QoL refers to the physical, psychological and social domains of health that are influenced by a person’s experiences, beliefs, expectations and perceptions 8.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The physical and psychosocial impairments in individuals with knee OA have an impact on QoL due to their influence on social interactions, mental functioning and sleep quality 7. QoL refers to the physical, psychological and social domains of health that are influenced by a person’s experiences, beliefs, expectations and perceptions 8.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with knee OA have inferior QoL compared with controls 7 9. Therefore, therapies that improve QoL in individuals with knee OA may mitigate the clinical, economic and social burden of this disorder 7. The purpose of this SR was to synthesise evidence of primary outcomes of randomised controlled trials (RCTs) examining the effect of treatment strategies on QoL or psychosocial factors in individuals with knee OA.…”
Section: Introductionmentioning
confidence: 99%
“…one hundred and twenty four 65 years) were randomized to therapeutic exercise (n =62) and conventional ression analysis revealed that age and BMI factors play a role in knee The present study highlights the various factors that influence physical disability and thereby demonstrates to clinical researchers and practitioners nderstanding and improving the quality of being goes beyond simply treating the Quality of life, Exercises, Osteoarthritis (OA) causes disability affecting approximately 12% of those between 25-74 years of age. [1,2]. Knee OA is multifactorial and can be divided into endogenous and exogenous risk factors.…”
Section: Mrsmegala Devimentioning
confidence: 99%
“…Osteoarthritis (OA) causes disability affecting approximately 12% of those between 25 age. [1,2]. Knee OA is multifactorial and can be divided into endogenous and exogenous risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Knee osteoarthritis (OA) is a prevalent condition that is associated with considerable pain, functional limitations and reduced overall quality of life . Knee OA can occur in either the patellofemoral joint (PF), the tibiofemoral joint (TF), or both.…”
mentioning
confidence: 99%